Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

Continuous table tennis is associated with processing in frontal brain areas: an EEG approach - Visser, Anton; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Experimental Brain Research)
Abstract Coordinative challenging exercises in changing environments referred to as open-skill exercises seem to be beneficial on cognitive function. Although electroencephalographic research allows to investigate changes in cortical processing during movement, information about cortical dynamics during open-skill exercise is lacking. Therefore, the present study examines frontal brain activation during table tennis as an open-skill exercise compared to cycling exercise and a cognitive task. 21 healthy young adults conducted three blocks of table tennis, cycling and n-back task. Throughout the experiment, cortical activity was measured using 64-channel EEG system connected to a wireless amplifier. Cortical activity was analyzed calculating theta power (4–7.5 Hz) in frontocentral clusters revealed from independent component analysis. Repeated measures ANOVA was used to identify within subject differences between conditions (table tennis, cycling, n-back; p < .05). ANOVA revealed main-effects of condition on theta power in frontal ( p < .01, η p 2 = 0.35) and frontocentral ( p < .01, η p 2 = 0.39) brain areas. Post-hoc tests revealed increased theta power in table tennis compared to cycling in frontal brain areas ( p < .05, d = 1.42). In frontocentral brain areas, theta power was significant higher in table tennis compared to cycling ( p < .01, d = 1.03) and table tennis compared to the cognitive task ( p < .01, d = 1.06). Increases in theta power during continuous table tennis may reflect the increased demands in perception and processing of environmental stimuli during open-skill exercise. This study provides important insights that support the beneficial effect of open-skill exercise on brain function and suggest that using open-skill exercise may serve as an intervention to induce activation of the frontal cortex.
Keywords: General Neuroscience

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Effects of surface instability on cortical information processing during multi- joint compound movements: an exploratory EEG study - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Performance and Brain Activity in Older Adults while Playing Leaning and Stepping Exergames - Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen

A combined flue gas cleaning system with a novel entrained flow SCR using an online synthesized catalyst (Poster) - Beimdiek, Janis; Schmid, Hans-Joachim
Keywords: clean air; harmful gas removal; denitrification; SCR; catalytic filtration; nanoparticles; flame-synthesis

Innovative Werkstoffherstellung für das Polymer Laser Sintern – Teil 2 - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Jesinghausen, Steffen; Schmid, Hans-Joachim (Werkstoffe)

Innovative Werkstoffherstellung für das Polymer Laser Sintern – Teil 1 - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Jesinghausen, Steffen; Schmid, Hans-Joachim (Werkstoffe)

Novel entrained flow SCR using online synthesized catalyst particles (Poster) - Beimdiek, Janis; Schmid, Hans-Joachim
Keywords: clean air; harmful gas removal; denitrification; SCR; catalytic filtration; nanoparticles; flame-synthesis

Continuous Situation-specific Development of Business Models: Knowledge Provision, Method Composition, Method Enactment - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a continuous challenging activity where different tasks need to be performed, and business decisions need to be made. Both have to fit the constantly changeable situation in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, a method for developing situation-specific business models is needed. As a solution, we refine the concept of situational method engineering (SME) to business model development. SME, in turn, provides means to construct situation-specific development methods out of fragments from a method repository. We develop a concept for the continuous situation-specific development of business models based on design science. The approach uses the roles of a domain expert, a method engineer, and a business developer together with a repository with method fragments for developing business models and a repository with modeling artifacts for supporting the development. Both repositories are filled by utilizing the experience of domain experts. Out of these repositories, situation-specific development methods for developing business models can be continuously composed based on the changeable situation by the method engineer and enacted by the business developer. We implement it as an open-source tool and evaluate its applicability in an industrial case study of developing a business model for a local event platform. Our results show that situation awareness supports the continuous development of business models.
Keywords: Business Model Development; Situational Method Engineering; Situation-specific; Business Model Canvas; Continuous Development

Towards Situation-specific Software Support for Cross-organizational Design Thinking Processes - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 5th International Workshop on Software-intensive Business (IWSiB'22))
Due to the increasing influences of a VUCA world, design thinking workshops have been established as a standard technique to build solutions according to uncertain customer needs. Concerning the ongoing pandemic and rising development of solutions across organizations, more and more workshops were conducted online with software support. However, existing software tools insufficiently address the different workshop situations in terms of the process (i.e., fixed tasks to conduct), the place (e.g., static online whiteboards), and people (i.e., synchronous working of all stakeholders). Therefore, we propose a design science study to develop a situation-specific software support that can be configured with flexible development processes, different places, and task-related people. Based on practical experience in existing research projects, we derive the initial design requirements and map them to a set of design principles. Out of that, we design a concept with its implementation as a software tool and point out open challenges.
Keywords: design thinking; situation-specific; cross-organizational; software support

Gamification-based UML Learning Environment in Virtual Reality - Yigitbas, Enes; Schmidt, Maximilian; Bucchiarone, Antonio; Gottschalk, Sebastian; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems (MODELS 2022))

Comparative Evaluation of AR-based, VR-based, and Traditional Basic Life Support Training - Yigitbas, Enes; Krois, Sebastian; Renzelmann, Timo; Engels, Gregor (Proceedings of the 10th International Conference on Serious Games and Applications for Health (SeGAH'22))

Human-in-the-Loop Large-Scale Model Transformations with the VICToRy Debugger - Weidmann, Nils; Yigitbas, Enes; Anjorin, Anthony; Srivastava, Ankita; Jose, Jane (The Journal of Object Technology)

Competitive Routing in Hybrid Communications Networks and Message efficient SetCover in AdHoc Networks - Kolb, Christina

Zu den Auswirkungen von Big Data auf personalisierte Angebote in digitalen Märkten - eine wettbewerbspolitische Analyse - Sowinski, Olivia

Zu den Vor- und Nachteilen von Luftfahrtallianzen - Eine wettbewerbspolitische Perspektive auf den Alleingang von Emirates - Schmidt, Thomas

An Economic Analysis of Mergers and Aquisitions - The case of Facebook and WhatsApp - Yeboah, Amoabeng

A self-stabilizing Hashed Patricia Trie - Knollmann, Till; Scheideler, Christian (Information and Computation)
While many research in distributed computing has covered solutions for self-stabilizing computing and topologies, there is far less work on self-stabilization for distributed data structures. However, when peers in peer-to-peer networks crash, a distributed data structure may not remain intact. We present a self-stabilizing protocol for a distributed data structure called the Hashed Patricia Trie (Kniesburges and Scheideler WALCOM'11) that enables efficient prefix search on a set of keys. The data structure has many applications while offering low overhead and efficient operations when embedded on top of a Distributed Hash Table. Especially, longest prefix matching for x can be done in O(log |x|) hash table read accesses. We show how to maintain the structure in a self-stabilizing way, while assuring a low overhead in a legal state and an asymptotically optimal memory demand of O(d) bits, where d is the number of bits needed for storing all keys.

Untersuchung von kleinskaligen Flüssigkeitselementen auf mikrostrukturierten Packungsoberflächen - Dechert, Christopher; Kenig, Eugeny